Harnessing knowledge of animal behavior to improve habitat restoration outcomes. Issue 4 (9th April 2020) - Hale, Robin; Blumstein, Daniel T.; Mac Nally, Ralph; Swearer, Stephen E.
Abstract: Restoring degraded habitat to increase biodiversity is a global challenge. While habitat restoration for animals should lead to self‐sustaining breeding populations of target species, often this does not occur. Understanding the factors constraining progress toward this goal and how these constraints can be overcome is vital. We use a review to highlight how insights from animal behavior can help plan restoration projects, and identify and ameliorate some of the reasons why restoration may fail to meet biodiversity goals. We present a decision tree to highlight how behavioral knowledge can identify and address two ways in which restoration can fail when: (1) target animals do not colonize restored sites and (2) they colonize restored sites but experience conditions that do not match their habitat requirements. Investing in the collection of behavioral information may be difficult for management agencies when funding is limited. We highlight when behavioral information is likely to be most important, and some of the practical considerations for its application in restoration projects. We conclude by identifying key knowledge gaps and future directions that can improve restoration outcomes for biodiversity by incorporating behavioral knowledge. Restoration is needed to ameliorate the effects of habitat loss, degradation, and fragmentation on fauna. Unfortunately, restoration does not always lead to the intended optimal outcomes for target animals. A greater consideration of animal behavior and its consequences can help during both the planning and evaluation of restoration projects. We hope to stimulate dialogue between restoration and behavioral ecologists to improve restoration outcomes for animals.